2007
DOI: 10.1109/lpt.2007.895066
|View full text |Cite
|
Sign up to set email alerts
|

Angle Selective Enhancement of Beam Deflection in High-Speed Electrooptic Switches

Abstract: Fast electrooptic (EO) deflector switches (DSs) have high potential for applications in optical burst transport networks. EO properties of active materials used in the DSs can impose some limitations on their beam deflection efficiencies. Using a test setup with planar silica waveguide microlens arrays, thin-film ferroelectric oxide beam deflectors, and glass volume Bragg gratings, we demonstrate that the beam deflection angle can be increased by more than a factor of 5 for the same switching voltages. The tec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
5
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 9 publications
1
5
0
Order By: Relevance
“…We confirmed that the coupling rising and falling times were comparable for all five channels. This result is well explained by (1), which means the deflection angle is proportional to the applied voltage. We calculated that the maximum number of resolvable spots of the KTN deflector at this wavelength (1.06 μm) and beam diameter (0.5 mm) exceeds 30.…”
supporting
confidence: 56%
See 1 more Smart Citation
“…We confirmed that the coupling rising and falling times were comparable for all five channels. This result is well explained by (1), which means the deflection angle is proportional to the applied voltage. We calculated that the maximum number of resolvable spots of the KTN deflector at this wavelength (1.06 μm) and beam diameter (0.5 mm) exceeds 30.…”
supporting
confidence: 56%
“…An EO deflector deflects a launched optical beam to switch between spatially arranged output channels using an applied voltage. (Pb, La)(Zr, Ti)O 3 (PLZT), LiNbO 3 (LN) and LiTaO 3 (LT) with prism structures are commonly used to realise multi-channel and high-speed EO switches [1][2][3]. A potassium tantalate niobate (KTa 1-x Nb x O 3 , KTN) single crystal is also a promising material for an EO deflector because of its huge second-order EO (Kerr) effect.…”
mentioning
confidence: 99%
“…Deflection of an incident beam for a small angle (it can be in milliradian range) leads to deflection of a diffracted beam for a predetermined arbitrary large angle. This phenomenon is the basis for high speed non-mechanical beam steering in high power laser systems [26] and in portable opto-electronic devices [27].…”
Section: Beam Deflectionmentioning
confidence: 99%
“…7 Such approach for angular magnification in fast electro-optical switches was demonstrated and has shown dramatic decrease of their size. 33…”
Section: Angular Narrowing and Steering Of Laser Beamsmentioning
confidence: 99%